2020
DOI: 10.1111/coa.13571
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for the outcome of Bells' palsy: A cohort register‐based study

Abstract: Objectives There is a lack of data on patients' and diagnostic factors for prognostication of complete recovery in patients with Bell's palsy. Design and setting Cohort register‐based study of 368 patients with Bell's palsy and uniform diagnostics and standardised treatment in a university hospital from 2007 to 2017 (49% female, median age: 51 years). Main outcome measures Clinical data, facial grading, electrodiagnostics, motor function tests, non‐motor function tests and onset of prednisolone therapy were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
3
23
0
2
Order By: Relevance
“…Even after Bell's palsy, an often underestimated disease, a fifth of the patients develops PFS 25 . Independent of the underlying etiology, facial palsy in general is not a disease with gender predominance 26,27 . Similar to the present study, most publications on series of PFS patients report of a weak to moderate predominance of women of between 55% and 75% 28,29 .…”
Section: Discussionsupporting
confidence: 84%
“…Even after Bell's palsy, an often underestimated disease, a fifth of the patients develops PFS 25 . Independent of the underlying etiology, facial palsy in general is not a disease with gender predominance 26,27 . Similar to the present study, most publications on series of PFS patients report of a weak to moderate predominance of women of between 55% and 75% 28,29 .…”
Section: Discussionsupporting
confidence: 84%
“…To overcome this limitation, Kaplan-Meier statistics were used to determine the probability of complete recovery over time. which started within a time window of 96 h after onset, had the highest probability of complete recovery [15].…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…Although corticosteroids are one of the mainstays of treatment in severe and critical COVID-19, it is not recommended in patients with mild and moderate symptoms due to potential disease exacerbation [ 9 , 10 ]. It seems that facial palsy associated with COVID-19 should be treated based on each patient's medical condition, as worse motor function based on House–Brackmann decreases the probability of complete recovery [ 11 , 12 ]. Goh et al reported a case of facial palsy 6 days after disease onset.…”
Section: Discussionmentioning
confidence: 99%